CBSE Class 9CBSE
Share
Notifications

View all notifications

Simplify the Following Expressions: (3 + Sqrt3)(3 - Sqrt3) - CBSE Class 9 - Mathematics

Login
Create free account


      Forgot password?

Question

Simplify the following expressions:

`(3 + sqrt3)(3 - sqrt3)`

Solution

We know that `(a - b)(a + b) = a^2 - b^2`. We will use this property to simplify the expression

`(3 + sqrt3)(3 - sqrt3)`

`∴ (3 + sqrt3)(3 - sqrt3) = (3)^2 - (sqrt3)^2`

`= 3^2 - sqrt3 xx sqrt3`

`= 3 xx 3 - sqrt(3 xx 3)`

`= 9 - (3^2)^(1/2)`

`= 9 - 3^1`

= 6

Hence the value of expression is 6.

 

  Is there an error in this question or solution?

APPEARS IN

Video TutorialsVIEW ALL [1]

Solution Simplify the Following Expressions: (3 + Sqrt3)(3 - Sqrt3) Concept: Operations on Real Numbers.
S
View in app×